FRI0147 IgG4 antibody response upon long term treatment with adalimumab. (23rd January 2014) - van Schouwenburg, P.; Krieckaert, C.; Nurmohamed, M.; Rispens, T.; Aarden, L.; Wouters, D.; Wolbink, G.
Abstract : Background: A substantial part of the rheumatoid arthritis (RA) patients is chronically treated with adalimumab. Some of these patients produce antibodies against adalimumab, which correlate with lower serum drug levels and reduced clinical response. Long term exposure to antigens may result in antigen specific IgG4 production as demonstrated in previous studies on prolonged exposure to antigens such as bee venom, factor VIII and IFN-β. Objectives: Here we investigate whether long term treatment of RA patients with the therapeutic monoclonal antibody adalimumab leads to the production of specific IgG4 antibodies. Methods: We developed radio immunoassays to detect total IgG or IgG4 against adalimumab and applied these in a cohort of 272 RA patients during three years of adalimumab treatment. Results: Of the 272 patients 32% developed antibodies against adalimumab. We observed that a fast majority of the patients also produce IgG4 antibodies against adalimumab (29%). The proportion IgG4 of total IgG against adalimumab varies widely between patients (median; 25-75 percentile 38; 21-67%). In some patients the antibody response even seems to be dominated by IgG4. Conclusions: The role of IgG4 in the immune response against adalimumab is variable in adalimumab treated RA patients. Although IgG4 is often considered to be harmless, because of its lack of effector function, these patients show low adalimumab levels and reduced clinical response. Disclosure of Interest: None Declared